The legacy of COVID-19: lessons and challenges for city-scale air quality management in the UK. (21st July 2021) - De Vito, Laura; Barnes, Jo; Longhurst, James; Williams, Ben; Hayes, Enda
ABSTRACT: The lockdown enforced by the UK Government to prevent the spread of the SARS-CoV-2 virus has led to an unparalleled reduction in traffic volumes and significant drop in nitrogen dioxide concentrations in most cities, although the picture emerging from residential emissions of particulate matter (PM10 and PM2.5 ) is more complex. The scale and degree of the intervention have exposed the level of change required to reduce pollution. Learning from the COVID-19 crisis, we identify three challenges that must be overcome to improve air quality in cities. First, what measures would be effective that balance civil liberties with enforcement action on air pollution? Second, how do we consolidate the cultural change needed to retain and normalise the social practices driving the observed pollution reduction? Third, how do we tackle these challenges in a way that breaks current patterns of socio-economic, health and environmental inequality?